2007
DOI: 10.1152/ajpendo.00172.2006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of islet inducible nitric oxide synthase and inhibition of glucose-stimulated insulin release after long-term lipid infusion in the rat is counteracted by PACAP27

Abstract: Qader SS, Jimenez-Feltström J, Ekelund M, Lundquist I, Salehi A. Expression of islet inducible nitric oxide synthase and inhibition of glucose-stimulated insulin release after long-term lipid infusion in the rat is counteracted by PACAP27. Am J Physiol Endocrinol Metab 292: E1447-E1455, 2007. First published January 30, 2007; doi:10.1152/ajpendo.00172.2006.-Chronic exposure of pancreatic islets to elevated plasma lipids (lipotoxicity) can lead to ␤-cell dysfunction, with overtime becoming irreversible. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 57 publications
4
24
1
Order By: Relevance
“…This was in marked contrast with the robust activation of iNOS by cytokines. These results are in contrast with previous suggestions that both glucose and palmitate induce iNOS in beta cell lines and rat islets [19][20][21][22]. Moreover, it was recently shown that induction of iNOS and consequently excessive generation of NO is responsible for the suppression of glucose-stimulated insulin secretion by palmitate; this was corrected by thiazolidinediones, probably through inhibition of G-protein-coupled receptor 40 (GPR40) [18].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…This was in marked contrast with the robust activation of iNOS by cytokines. These results are in contrast with previous suggestions that both glucose and palmitate induce iNOS in beta cell lines and rat islets [19][20][21][22]. Moreover, it was recently shown that induction of iNOS and consequently excessive generation of NO is responsible for the suppression of glucose-stimulated insulin secretion by palmitate; this was corrected by thiazolidinediones, probably through inhibition of G-protein-coupled receptor 40 (GPR40) [18].…”
Section: Discussioncontrasting
confidence: 93%
“…Several studies have suggested that exposure of islets to high glucose or NEFA levels induces production of inducible nitric oxide synthase (iNOS), causing attenuation of the insulin response to glucose [18][19][20][21][22]. Thus, iNOS-dependent NO generation with subsequent induction of ER stress could be the common denominator of beta cell apoptosis induced by inflammatory cytokines and glucolipotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…However, in islet b-cells, knowledge concerning the role of ubiquitinproteasome pathway in iNOS protein degradation is very limited. Pituitary adenylate cyclase-activating polypeptide 27, a cAMP-producing peptide suppressed iNOS expression in lipid-infused rat islets, which was not reversed by the treatment of a proteasome inhibitor MG 132 (Qader et al 2007). Additionally, MG132 did not reverse the GLP-1-induced suppression of iNOS expression in diabetic GK rat islets, but instead MG132 induced loss of iNOS protein (Salehi et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…We found that an ADP analogue reduced cAMP levels and blocking the P2Y 13 receptor with MRS2211 restored cAMP levels in beta cells. cAMP has been shown to improve insulin release and to protect against apoptosis and cell death [24]. Interestingly, the adenosine A 1 receptor is also Gα i -coupled and also decreases cAMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…The purity of each beta cell preparation was assessed by RIA measurement of insulin, glucagon, somatostatin and pancreatic polypeptide per mg protein [24]. At least 10 samples (tubes) of the cells were examined for each hormone.…”
Section: Methodsmentioning
confidence: 99%